Socio-Scientific Issue Module Based on Pros and Cons of Using Pesticides in Citrus nobilis Cultivation for Enhancing Students Awareness in Preserving the Environment - Priyanka*, Luh Mitha; Muderawan, I Wayan; Suparta, I Nengah; Bgeholz, Susanne; Matthiesen, Finn (Jurnal Pendidikan Sains Indonesia, 2025)
Environmental education is a critical government initiative in Indonesia, aiming to cultivate students' environmental awareness. Given the urgent need for students to engage with real-world environmental challenges, this study developed and evaluated a socio-scientific issues (SSI)-based module. The module's primary goal was to deepen students' understanding of local environmental problems and encourage their active participation in preservation efforts. A Research and Development approach, specifically the ADDIE model (analysis, design, development, implementation, and evaluation), guided this research. Data collection utilizes quantitative and qualitative methods. Qualitative data included insights from validation sheets and response questionnaires completed by expert lecturers and students. Quantitative data, in the form of essay questions, were gathered through pre- and post-tests to assess changes in students' environmental awareness after module implementation. The results demonstrated the SSI module's strong validity and effectiveness. Three expert lecturers rated the module with an average validity score of 85, categorized as "good," affirming its sound pedagogical and scientific design. Student evaluations were also overwhelmingly positive, yielding an average score of 89, placing it in the "very good" category. Crucially, the module significantly increased students' awareness of environmental problems. Quantitatively, the average student score rose from 81.25 in the pre-module assessment to 86.25 post-module engagement. These findings highlight the SSI module as an effective and valuable tool for empowering students to learn about and contribute to environmental preservation